Quashing Demand Criminalizing Clients? Evidence from the UK - Marina Della Giusta; Maria Laura Di Tommaso; Sarah Jewell; Francesca Bettio (Institute of Labor Economics (IZA), 2019)
We discuss changes in the demand for paid sex accompanying the criminalization of prostitution in the United Kingdom, which moved from a relatively permissive regime under the Wolfenden Report of 1960, to a much harder line of aiming to crack down on prostitution with the Prostitution (Public Places) Scotland Act 2007 and the Policing and Crime Act of 2009 in England and Wales. We make use of two waves of a representative survey, the British National Survey of Sexual Attitudes and Lifestyles (Natsal2, conducted in 2000-2001 and Natsal3, conducted in 2010-2012) to illustrate the changes in demand that have taken place across the two waves. We do not find demand decreasing in our sample and find a shift in the composition of demand towards more risky clients, which we discuss in the context of the current trends towards criminalization of prostitution.
Keywords: C35; J16; J22; K42; 330; criminalization; prostitution; demand